Diversity of selected toll-like receptor genes in cheetahs (Acinonyx jubatus) and African leopards (Panthera pardus pardus) - Meißner, René; Mokgokong, Prudent; Pretorius, Chantelle; Winter, Sven; Labuschagne, Kim; Kotze, Antoinette; Prost, Stefan; Horin, Petr; Dalton, Desire; Burger, Pamela A (Scientific reports, 2024)
The anthropogenic impact on wildlife is ever increasing. With shrinking habitats, wild populations are being pushed to co-exist in proximity to humans leading to an increased threat of infectious diseases. Therefore, understanding the immune system of a species is key to assess its resilience in a changing environment. The innate immune system (IIS) is the body's first line of defense against pathogens. High variability in IIS genes, like toll-like receptor (TLR) genes, appears to be associated with resistance to infectious diseases. However, few studies have investigated diversity in TLR genes in vulnerable species for conservation. Large predators are threatened globally including leopards and cheetahs, both listed as 'vulnerable' by IUCN. To examine IIS diversity in these sympatric species, we used next-generation-sequencing to compare selected TLR genes in African leopards and cheetahs. Despite differences, both species show some TLR haplotype similarity. Historic cheetahs from all subspecies exhibit greater genetic diversity than modern Southern African cheetahs. The diversity in investigated TLR genes is lower in modern Southern African cheetahs than in African leopards. Compared to historic cheetah data and other subspecies, a more recent population decline might explain the observed genetic impoverishment of TLR genes in modern Southern African cheetahs. However, this may not yet impact the health of this cheetah subspecies.
Keywords: Animals, Wild; Acinonyx; infekční nemoci; Communicable Diseases; Panthera; divoká zvířata; Humans; Animals; lidé; zvířata; ekosystém; Ecosystem